2012
DOI: 10.1128/jcm.05964-11
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Features Differentiating Bovine, Food, and Human Isolates of Shiga Toxin-Producing Escherichia coli O157 in The Netherlands

Abstract: The frequency of Escherichia coli O157 genotypes among bovine, food, and human clinical isolates from The Netherlands was studied. Genotyping included the lineage-specific polymorphism assay (LSPA6), the Shiga-toxin-encoding bacteriophage insertion site assay (SBI), and PCR detection and/or subtyping of virulence factors and markers [stx1, stx 2a /stx 2c , q21/Q933, tir(A255T), and rhsA(C3468G)]. LSPA6 lineage II dominated among bovine isolates (63%), followed by lineage I/II (35.6%) and lineage I (1.4%). In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
2
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 45 publications
6
51
2
1
Order By: Relevance
“…Characterization of lineage types among E. coli O157 : H7 strains in Belgium revealed higher prevalence of lineage I/II among E. coli O157 : H7 strains analysed (70.6 %). This finding is consistent with previous studies that reported the higher frequency of distribution of this lineage among tested E. coli O157 : H7 strains from the Netherlands (55.1 %), Argentina (90 %) and Australia (88 %) (Franz et al, 2012;Mellor et al, 2012). This lineage has been shown to share characteristics of both lineage I and lineage II, but has been presented to cause human illness at frequencies similar to those of lineage I strain and includes a hyper-virulent isolate of which multistate 'spinach' outbreak strains are representative Ziebell et al, 2008).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Characterization of lineage types among E. coli O157 : H7 strains in Belgium revealed higher prevalence of lineage I/II among E. coli O157 : H7 strains analysed (70.6 %). This finding is consistent with previous studies that reported the higher frequency of distribution of this lineage among tested E. coli O157 : H7 strains from the Netherlands (55.1 %), Argentina (90 %) and Australia (88 %) (Franz et al, 2012;Mellor et al, 2012). This lineage has been shown to share characteristics of both lineage I and lineage II, but has been presented to cause human illness at frequencies similar to those of lineage I strain and includes a hyper-virulent isolate of which multistate 'spinach' outbreak strains are representative Ziebell et al, 2008).…”
Section: Discussionsupporting
confidence: 83%
“…Molecular typing and microbial genomics have facilitated the characterization and comparison of E. coli O157 : H7 strains recovered from different isolation sources demonstrating non-random distribution of genotypes among clinical and non-clinical strains (Besser et al, 2008;Franz et al, 2012;Hartzell et al, 2011;Lee et al, 2011;Whitworth et al, 2010;Yang et al, 2004;Yokoyama et al, 2011;Zhang et al, 2010;Ziebell et al, 2008). In addition, several epidemiological studies supported the growing evidence of substantial variability in the virulence of E. coli O157 : H7 genotypes implicated in different outbreaks and variation in patient symptoms (Besser et al, 2008;Grant et al, 2008;Manning et al, 2008).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Whereas >90% of E. coli O157 isolates recovered from the beef chain in Ireland possessed vt and eae in combination, <10% of non-O157 VTEC serogroups fell into this category (38). In a Belgian study on O26, O103, O145, and O111 in cattle feces, about 6% of samples were positive and about 50% of isolates had key human virulence genes (47,48). A further study showed that for E. coli O157 genotypes associated with human illness a minor subpopulation was in the bovine reservoir.…”
Section: Bovine Carriage Of Vtecmentioning
confidence: 99%
“…A further study showed that for E. coli O157 genotypes associated with human illness a minor subpopulation was in the bovine reservoir. (47,48) This shows that while VTEC isolates in beef play a role in human illness, a risk assessment of their virulence potential is essential.…”
Section: Bovine Carriage Of Vtecmentioning
confidence: 99%